Peculiarities of the adaptation mechanism of enterprises to the challenges of the external environment - Полозова, Т. В.; Куценко, Ю. А. (ХНУРЕ, 2021)
The process of making managerial decisions at domestic enterprises is significantly complicated in the current conditions of the country's transformational economy. This is due to the high level of uncertainty and instability of the business environment in which businesses operate and interact. The relevance of the chosen topic is due to the current state of the transformational economy of Ukraine and the need to form a mechanism for adaptation of industrial enterprises to environmental conditions
DOI: 10.30837/978-966-659-334-7
Keywords: adaptation; managerial decisions; external environment